Analisis WMCC (Weighted Marginal Cost of Capital) sebagai Indikator Optimalisasi Struktur Modal pada Perusahaan Manufaktur di Indonesia - Rr. Ajeng Jelita Cahya Lazuardyne; Yeni Lita Sari; Naila Aqidatul Ulya; Fitria Nabila; Nikmatul Husnah (BADAN PENERBIT STIEPARI PRESS, 2025)
Determining the optimal capital structure is a critical element in corporate financial decision-making, particularly in capital-intensive sectors such as manufacturing. This study aims to examine the role of Weighted Marginal Cost of Capital (WMCC) as an evaluative indicator for optimizing capital structure in Indonesian manufacturing companies. A literature review approach was employed by analyzing 26 relevant national and international journals, both theoretically and contextually. The findings indicate that WMCC offers a more accurate assessment of additional financing efficiency compared to WACC, as it reflects the marginal cost of each new unit of capital raised. Key factors influencing WMCC include corporate governance, risk disclosure, macroeconomic stability, and ownership structure. These results imply the need for adopting WMCC in corporate financial management as a more precise foundation for evaluating investment decisions and funding strategies.